Chemical constituents from Piper betle L. Var Nigra (Piperaceae) - Fajar Prasetya; Supriatno Salam; Agung Rahmadani; Hadi Kuncoro; Rolan Rusli; Afif Ruchaemi; Sukartiningsih Sukartiningsih (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2021)
Two fatty acid derivatives, 2-octenoic acid and 2-hexenoic acid were isolated from the extract of n-hexane of the Piper betle L. Var. Nigra (Piperaceae). The chemical structures were identified on the basis of spectroscopic evidence and compared to previously reported spectra. These isolated compounds appear for the first time in the plant.